KEKUATAN HUKUM PEMBUKTIAN SURAT HIBAH ATAS PERALIHAN TANAH PERTANIAN (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 2771 K/PDT/2010) - BEBI MUHASNAH (PREMISE LAW JURNAL, 2016)
Transfer on farm land rights which is caused by a legal action (legal act) in the form of hibah (grant) written in a certificate and stamped with seal in 1935 before the adat and religious leaders in the adat meeting and was agreed by all heirs has met the requirement determined by the Minangkabau customary law. The research used judicial normative method which was aimed to study legal provisions, norms which were referred to regulations, legal principles, and court’s verdicts relating to the force of legal evidence of the hibah certificate. The result of the research shows that the legal force of the evidence on the hibah certificate, relating to the Supreme Court’s Ruling No. 2771 K/PDT/2010, is stated as the initial written evidence. It means that the hibah certificate is valid as written evidence which also means that it is valid as an underhanded deed which has met formal requirement for a legal act Keywords: Evidence, Hibah Certificate, Land Rights Transfer